2015
DOI: 10.1186/s13069-015-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of angiotensin II signaling in the prevention of fibrosis

Abstract: Over the last decade, it has become clear that the role of angiotensin II extends far beyond recognized renal and cardiovascular effects. The presence of an autologous renin-angiotensin system has been demonstrated in almost all tissues of the body. It is now known that angiotensin II acts both independently and in synergy with TGF-beta to induce fibrosis via the angiotensin type 1 receptor (AT1) in a multitude of tissues outside of the cardiovascular and renal systems, including pulmonary fibrosis, intra-abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 96 publications
0
119
0
1
Order By: Relevance
“…TGF-β1 plays a vital role in preserving ECM, inducing fibroblast proliferation and transforming fibroblasts into myofibroblasts 24 . Activated fibroblasts deposit collagen I, an important component of ECM, which causes the thickening of the alveolar walls 30 .…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 plays a vital role in preserving ECM, inducing fibroblast proliferation and transforming fibroblasts into myofibroblasts 24 . Activated fibroblasts deposit collagen I, an important component of ECM, which causes the thickening of the alveolar walls 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the functions of RAS signalling extend beyond cardiovascular homeostasis. As discussed earlier, RAS activation is also involved in tumour and fibrosis development (Ager et al 2008, Murphy et al 2015. Epidemiological studies provide evidence that RAS inhibition may reduce tumour development and progression (Ager et al 2008).…”
Section: Other Antifibrotic Agentsmentioning
confidence: 92%
“…Next to immune system, tissue hypoxia and activation of the renin-angiotensin system (RAS) are also shown to be present in many fibrotic diseases such as cardiac and hepatic fibrosis (Wynn 2008). Angiotensin II is able to induce fibrosis via the AT1 receptor and increased expression of profibrotic growth factors such as TGFβ, FGF2 and PDGF (Ager et al 2008, Murphy et al 2015. Furthermore, overexpression of AT1 receptor is found in many malignancies, linking RAS to tumour and fibrosis development (Ager et al 2008).…”
Section: Learning From Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to new novel mechanistic insights, hydralazine may has to be re-visited in comparison to inhibitors of the renin-angiotensinaldosterone system (RAAS) such as angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs). Today RAAS-inhibitors are the gold-standard in therapy of hypertension, chronic heart failure and proteinuric kidney diseases, because numerous large controlled clinical trials demonstrated efficacy in reducing blood pressure, but also in improving chronic heart failure and in reducing cardiovascular mortality and in reducing proteinuria and improving outcome of proteinuric chronic kidney diseases shortly after their introduction to clinical use [40,[46][47][48][49]. In comparison, hydralazine was introduced to the clinic in 1952, before the age of modern clinical trials, and the first small controlled clinical study on efficacy of hydralazine in hypertension was not reported before 1964 [50].…”
Section: Hydralazine Revisitedmentioning
confidence: 99%